Resilience: A Review Literature - รุ่งเรืองกลกิจ สมพร; โคตนารา อิงคฎา (วารสารพยาบาลศาสตร์และสุขภาพ, 2012)
Objective This review paper aims to describethe definition, condition, factors, measurements, andsuggestions to study resilience from a Thai perspective.Methods A literature review of the concepts,research methods, and past theses was conducted fromMEDLINE PLUS Health Information, ELSEVIERFULL-TEXT ARTICLE, PubMED Central, UKPubMed Central, Full Test RNA, COS ScholorUniverse, SpringerLink, Ovid Technologies, Inc.,ProQuest, Science Direct, Cambridge Journal Online,Questia-The Online Library of Books and Journals,SAGE Journal online, Google, EBSCO, WILEY interScience databases and Thai lists which published during1990-2008. Resilience was used as the searchkeyword. Family resilience was excluded from thisreview. A total of 51 full papers were selected, including46 English and 5 Thai publications.Results Resilience has been studied to understandthe adaptation process when people face with adversityand have positive outcomes. Resilience is a dynamicprocess which involves many factors that interacts witheach other. Resilience is changeable in time, context,and has individual differences. Conclusion A suitablemeans to study the definition, attribution, and terms todescribe people who have resilience characteristic withinthe Thai context would be by conducting a qualitativeresearch. In addition, a qualitative research is appropriateto study the process of resilience. A quantitative researchhowever, is helpful to understand how the risk andprotective factors contribute to resilience, usingadvanced statistics such as multivariate research. It isimportant to assess the risks and protective factors ofvulnerable groups before conducting an interventionprogram to enhance resilience.